ASSESSMENT OF PERIODIC DISSIMILARITY OF PHYTOCHEMICAL AND ANTIDIARRHEAL ACTIVITY OF ETHANOLIC EXTRACT OF PSIDIUM GUAJAVA LINN (MYRTACEAE) LEAVES USING WISTAR ALBINO RATS - Borah, Uttam; Dash, Biswajit; Chakraborty, Jashabir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The current investigation was achieved to treasure out the modification of antidiarrheal activity of ethanoic leaves extract of Psidium guajava Linn. with respect to change of season, namely, autumn and spring. Methods: The castor oil induced diarrhea method is employed for assessment of periodic dissimilarity of antidiarrheal activity of ethanolic extract of P. guajava Linn. (Myrtaceae) leaves. Phytochemical variation is resolute as per typical procedure using various reagents. Results: Phytochemical scrutiny discloses that small fluctuation of phytoconstituent content was observed. The extract was initially assayed for its possessions in castor oil-induced diarrhea at different doses (200, 400, and 600 mg/kg, p.o.). There was statistically noteworthy lessening (p<0.05) in the number of wet feces by 78.33% during spring season and 78.26% during autumn season at 600 mg/kg body weight, and when compared to negative control rats, which might be due to change in climate or due to alteration in plant biosynthesis pathway in different season. Conclusion: The outcomes deliver the suggestion for variation in phytochemical contents as well as amendment in antidiarrheal activity of ethanoic extract of P. guajava leaves during autumn and spring.